KUBUR BATU (RETI) DI KAMPUNG KAWANGU KECAMATAN PANDAWAI KABUPATEN SUMBA TIMUR PROVINSI NUSA TENGGARA TIMUR - Ayu Vidya Trisna Prilyandani, Ni Nyoman; Ardika, I Wayan; Palupi Titasari, Coleta (Humanis; Volume 16. No. 2. Agustus 2016, 2016)
Tradition is an activity carried for generations. The remains of the megalithic tradition in Kawangu village, District Pandawai, East Sumba in the form of stone tomb (reti) with a decorative menhirs (penji). This research was conducted to determine the type of form by classification based on size. Burial systems in reti in Kawangu village are unique because burial placed on the stone above the ground level. Reti has significance for society of Kawangu.This research uses multiple methods of data collection, data analysis, and theory to answer the problem of research The method used in this study includes data collection phase and data processing. The data collection phase in the form of observation, interview, and literature study, while the data processing stage performance by using the typology analysis and ethnography. The theory is used to help answer the problem of this research is the theory of structural functionalism and semiotics.Results of the analysis of the data obtained in the form of reti in Kawangu Village form consists of 2 larges size which can be classified according ornament of menhirs (penji), 18 mediums size that can be classified based on the material are limestone and cement, and 19 smalls size. Burial system made on the ground symbolizing the great king and meaning of power and serve as a place of worship, and a tribute to the ancestor. Kawangu megalithic tradition in the village can be called as a living megalithic tradition because it still continues to this day.